Economic and Psychological Factors in Determining Accounting Students’ Interest in Pursuing Careers as Public Accountants - syurmita; Hanafi, Yusuf; Ghoni, M.Abdul (Jurnal Manajemen Pendidikan, 2025)
Background: The public accounting profession plays an important role in ensuring the reliability of financial information. However, not all accounting students are interested in pursuing careers as public accountants. Understanding the factors that influence students’ career interest is important for accounting education and the development of the accounting profession. Purpose: This study aims to examine the influence of financial rewards, professional recognition, job market considerations, emotional intelligence, and subjective norms on accounting students’ interest in pursuing careers as public accountants. Design/method/approach: This study uses a quantitative research approach. The data were collected through a questionnaire distributed to 100 accounting students from private universities in Jakarta using purposive sampling. The data were analyzed using multiple linear regression with the help of SPSS software. Results: The results show that financial rewards, professional recognition, and job market considerations have positive and significant effects on accounting students’ interest in pursuing careers as public accountants. Meanwhile, emotional intelligence and subjective norms do not have significant effects on students’ career interest. Contribution/value: This study contributes to accounting education research by providing empirical evidence on the factors influencing accounting students’ career choices. The findings highlight the importance of financial incentives and job market opportunities in shaping students’ interest in the public accounting profession.